Effects of porosity and thickness of porous sheets on heat transfer enhancement in a cross flow over heated cylinder - Al-Salem, Khaled; Öztop, Hakan Fehmi; Kiwan, Suhil (Pergamon-Elsevier Science Ltd, 2011)
An experimental study is carried out to investigate the thermal impact of wrapping an aluminum porous sheet over a circular tube in a heat convection configuration. The experimental apparatus consists of a heated horizontal cylinder with a constant heat flux. The cylinder is then covered with porous sheets of different thicknesses. The tube is exposed to a cross flow of air at different speeds which corresponds to different Reynolds numbers. The effect of the added porous layer on the pressure loss over the cylinder was also investigated. It is observed that heat transfer is greatly enhanced with the addition of the porous layer. Also, the addition of the porous layer doesn't appear to increase the pressure loss. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Porous layer; Heat exchanger; Heat transfer enhancement